Regional policy in Third World countries - Andreas Kopp (Intereconomics, 1983)
A great deal would suggest that the process of urbanisation in developing countries leads to both negative allocation effects and to an increase in income inequality between urban and rural districts. Regional policy measures almed at improving the lot of rural areas would seem called for. Which concepts exist on this issue and how are they to be rated?
Keywords: 330; Regional Development